The role of early stages of cortical visual processing in size and distance judgment: A transcranial direct current stimulation study - Costa, Thiago L.; Costa, Marcelo F.; Magalhães, Adsson; Rêgo, Gabriel G.; Nagy, Balázs V.; Boggio, Paulo S.; Ventura, Dora F. (Neuroscience letters, 2015)
•tDCS of the early visual cortex affects size but not distance judgment.•Increased visual cortex activity might interfere with size judgment.•Size and distance judgment involves different mechanisms. Recent research suggests that V1 plays an active role in the judgment of size and distance. Nevertheless, no research has been performed using direct brain stimulation to address this issue. We used transcranial direct-current stimulation (tDCS) to directly modulate the early stages of cortical visual processing while measuring size and distance perception with a psychophysical scaling method of magnitude estimation in a repeated-measures design. The subjects randomly received anodal, cathodal, and sham tDCS in separate sessions starting with size or distance judgment tasks. Power functions were fit to the size judgment data, whereas logarithmic functions were fit to distance judgment data. Slopes and R2 were compared with separate repeated-measures analyses of variance with two factors: task (size vs. distance) and tDCS (anodal vs. cathodal vs. sham). Anodal tDCS significantly decreased slopes, apparently interfering with size perception. No effects were found for distance perception. Consistent with previous studies, the results of the size task appeared to reflect a prothetic continuum, whereas the results of the distance task seemed to reflect a metathetic continuum. The differential effects of tDCS on these tasks may support the hypothesis that different physiological mechanisms underlie judgments on these two continua. The results further suggest the complex involvement of the early visual cortex in size judgment tasks that go beyond the simple representation of low-level stimulus properties. This supports predictive coding models and experimental findings that suggest that higher-order visual areas may inhibit incoming information from the early visual cortex through feedback connections when complex tasks are performed.